Surface structure analysis for the Bulalo Geothermal Field possible implications to local and regional tectonics - Aquino, Dennis Jerome Paras (2004)
The Bulalo geothermal Field (BGF) is the second largest geothermal field in the Philippines in terms of generative capacity. It is situated within the Macolod Corridor (MC), a postulated NE_SW rift zone that traverses the SW portion of Luzon Island. Quaternary volcanism in this region is influenced by convergent zones found on either side of the island; as well as diffuse structure systems that trend NE-SW, NW-SE, and N-S. Similarly, surface structures identified in the existing structural map of the BGF are mutually intersecting faults oriented mainly to the NE-SW or NW-SE. Surface structure analysis was carried out for the BGF to determine present-day stress patterns that influence the geometry and sense of movement of faults. Subsequent tectonic modeling will enable this study to infer: (1) how surface structures of the BGF affect the underlying geothermal system; and 92) how local BGF structures relate to the complex tectonics of the MC. Observations from geologic mapping, image processing, and structure reading synthesis indicate that majority of BGF surface structures follow the main tectonic grain of the MC, which is the NE direction. NE structures are mostly open or gaping fractures and steep, graben-forming normal faults. At least seven additional N-S trending lineaments were delineated from digital elevation models. outcrop-level evidence from youthful tuffaceous outcrops reveals that these previously unmapped N-S structures are dextral faults with minor components of normal displacement. NW-trending strcutures in teh BGF are not as prominent as the NE and N-S varieties. However some of the more relevant NW structures are compressional-regime thrust faults. A simple transtensional stress regime can account for the observed N-S dextral shearing, NE-oriented graeb faulting, and NW-trending thrust faulting in the surface rocks of the BGF. The geometry of these strcutures also point to a σ₃=̃ N65 ̊W. Both principal stress axes are in the horizontal plane. Transtension in the BGF implies that NE and N-S structures are extensional in nature, and should be the primary targets for reservoir permeability. This is an important observation since the most productive portion of the BGF, an area of enhanced permeability known as the "sweet spot", appears to be a zone bounded by intersecting NE and N-S faults. However, NW-trending faults are also known to enhance the permeability of the "seet spot". The apparent extensional characteristic of these NW structures is probably related to the morphological bend of the regional Philippine Fault Zone, and should not be confused with the localized transtensional stress regime of the BGF. The most reasonable tectonic model that would explain the arrangement of structural entities in the MC also has a horizontal σ₃parallel to the NW-SE. There are two possible sources of this NE-SW compressive stress, both of which are found in the west Philippine margin: (1) the subduction at the Manila trench; and/or (2) the postulated ongoing collision of the continental Palawan-Mindoro Terrane with the west Philippine margin.
"March 2004."
One folded map in pocket
Thesis (M.S. Geology)--University of the Philippines Diliman.
Keywords: Geothermal engineering; Geothermal power plants -- Philippines -- Luzon